Impact of fecal carriage of extended-spectrum beta-lactamase producing Enterobacteriaceae on the outcomes of transrectal needle biopsies of the prostate - (:unkn) unknown (My University, 2013)
Amaç: Bu çalışmada, transrektal prostat biyopsisi (TRPB) öncesi, hastalarda dışkıda geniş spektrumlu beta-laktamaz üreten Enterobacteriaceae (GSBL-ÜE) taşıyıcılığı oranları, risk faktörleri ve sonuçları gösterilmesi amaçlanmıştır. Hastalar ve Yöntem: Toplam 143 TRPB yapılan hasta çalışmaya alınmıştır. Bunların 33(%23)ünde GSBL-ÜE taşıyıcılığı bulunmuştur. Ortalama hasta yaşı 62 ± 7,5 (43-81)dir. Bulgular: Tek değişkenli analizle son 2 ayda kinolon veya başka bir antibiyotik kullanımı, prostatit ve diabetes mellitus (DM) GSBL-ÜE taşıyıcılığı ile ilşkili bulunmuştur. Çok değişkenli analiz, son 2 ayda kinolon kullanımı (OR: 4,865; CI: 1,45-16,1), ve DM (OR: 4,04; CI: 1,64-10) varlığını önemli faktörler olarak göstermiştir. TRPB sonrası disüri (p<0,001), ateş (p=0,046) ve üşüme-titreme (p=0,002) gelişmesi GSBL-ÜE taşıyıcılığı ile ilişkili bulunmuştur. Asemptomatik bakteriüri ve sepsis saptanmamıştır. Semptomatik üriner sistem infeksiyon oranı %19dur. Sonuç: Bu çalışma GSBL-ÜE taşıyıcılığı için biyopsi öncesi risk faktörlerinin son 2 ayda kinolon veya diğer antibiyotik kullanımı ve DM varlığı olduğunu göstermiştir. Ciddi infektif komplikasyonların düşük oranda olması nedeniyle profilaksi rejimlerinin değiştirilmesi önerilmemektedir.

Objective: This study aimed to address the prevalence, the risk factors and the results of fecal carriage of extended-spectrum beta- lactamase producing Enterobacteriaceae (ESBL-PE) in patients who had undergone transrectal needle biopsy of the prostate (TRNBP). Patients and Methods: A total of 143 patients who had undergone TRNBP were included. Of these, 33(23%) had fecal carriage of ESBL-PE. The mean age of the patients was 62 ± 7.5 (43-81) years. Results: A univariate analysis showed that quinolone or other antibiotic use within the last 2 months, prostatitis, and diabetes mellitus (DM) were significantly associated with the presence of ESBL-PE. A multivariate analysis showed that quinolone use within the past 2 months (OR: 4.865; CI: 1.45-16.1), and DM (OR: 4.04; CI: 1.64-10) were found to be significant. Development of dysuria (p<0.001), fever (p=0.046) and chills (p=0.002) after TRNBP were shown to be related to the presence of ESBL-PE . There was no asymptomatic bacteriuria and sepsis, the rate of symptomatic urinary tract infection was 19%. Conclusion: This study showed that pre-biopsy risk factors for the presence of ESBL-PE were quinolone or other antibiotic use within the last 2 months and presence of DM. Changing prophylactic regimens should not be recommended due to the low rate of severe complications.
Geniş spektrumlu beta laktamaz üreten Enterobacteriaceae taşıyıcılığının prostatın transrectal iğne biyopsisi sonuçlarına etkisi
Keywords: Genel ve Dahili Tıp